Variability of Rainfall Over the Coastal Area In Bangladesh by Using Climate Model - Islam, Shahana; Md Moniruzzaman, -; Mannan, MA (Journal of the Asiatic Society of Bangladesh, Science, 2021)
The study attempt to understand the variability of rainfall by looking into the previous and future climate of the coastal area in Bangladesh from 1850 to 2100 by using the climate model (CMCC-CM- the Centro Euro-Mediterraneo Sui Cambiamenti Climatici Climate Model) of the Fifth Assessment Report (AR5) of the Intergovernmental Panel on Climate Change (IPCC). Rainfall data were collected from CMCC-CM by R programming for two GHGs emission scenarios (RCP 4.5 and RCP 8.5) referred to as ‘Representative Concentration Pathways (RCPs)’. The analysis has been conducted based on four seasons and an annual basis by plotting model data in MS Excel and R programming. The model shows that the average annual rainfall will increase from 1055.6 mm (during 1850-1900) to 1368.1mm (during 2051-2100) for RCP 4.5 while it will reach 1569.7mm (during 2050-2100) for RCP 8.5. Rainfall is also increasing for all seasons except winter. In winter season, the average rainfall will increase from 35.37mm (during 1850-1900) to 41.75mm (during 2051-2100) for RCP 4.5, where it will decrease from 35.37mm (during 1850-1900) to 22.55mm (during 2051-2100) for RCP 8.5 in the study area. The increasing and decreasing trend are more in high GHGs emission scenarios than in the medium, which will be alarming. Accordingly, this projection will be helpful to understand the adverse impacts of climatic elements and take short and long-term planning of decision-makers in that area. J. Asiat. Soc. Bangladesh, Sci. 47(2): 149-160, December 2021